Design solutions for improving website quality and effectiveness - Sreedhar, G. (Advances in web technologies and engineering (AWTE) book series, 2016)
This book is an authoritative reference source for the latest breakthroughs, techniques, and research-based solutions for the overall improvement of the web designing process, featuring relevant coverage on the analytics, metrics, usage, and security aspects of web environments.